Air-side thermal hydraulic performance of microchannel heat exchangers with different fin configurations. (October 2017) - Saleem, Arslan; Kim, Man-Hoe
Highlights: Investigate air-side thermal hydraulic performance for microchannel heat exchangers. Local air-side heat transfer coefficient and pressure drop are addressed. Fin configuration with louver pitch of 1.0 mm has the maximum Nusslet number. Provide the effect of fin height on air-side thermal hydraulic performance. Abstract: This paper presents three-dimensional steady state analysis of compact multi-louvered fin and flat tube heat exchangers applicable in domestic and mobile air conditioning systems. Conjugate heat transfer analysis has been conducted for five geometric configurations of the heat exchanger based on the louver pitch values (0.8, 1.0, 1.4, 1.7 and 2.0 mm) in the laminar range of Reynolds number 50–450. For all geometric configurations, local air-side heat transfer coefficient and pressure drop are presented in terms of Colburn j factor and Fanning friction f factor, respectively. In addition, the effect of fin height on thermal hydraulic performance has also been addressed based on local Nusselt number distribution along the fin height. The results reveal that geometric configuration with the louver pitch of l.0 mm showed the highest average Nusselt number of 123% at the penalty of 116% pressure drop compared to louver pitch of 2.0 mm at the Reynolds number of 50.